Pengaruh Ekstrak Daun Pegagan (Centella Asiatica L.) terhadap Gambaran Histopatologi Testis Tikus Putih (Rattus Norvegicus) Jantan Galur yang Terpapar Asap Rokok - Asna Safitri; Mulyati Sri Rahayu; Iskandar Albin (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Cigarette smoke is a major source of free radicals that can cause various health problems, including disturbances in the male reproductive system. Nicotine and other harmful compounds in cigarettes increase oxidative stress and interfere with spermatogenesis. Gotu Kola (Centella asiatica) is a medicinal plant known for its antioxidant properties that may help neutralize free radicals. This study aimed to determine the effect of Gotu Kola leaf extract on the histopathological features of the testes in male Wistar rats exposed to cigarette smoke. An experimental study using a Post-Test Only Control Group Design was conducted on 24 rats divided into six groups: a normal group, a negative control group exposed to cigarette smoke, a positive control group treated with vitamin E, and three treatment groups receiving Gotu Kola extract at doses of 120, 180, and 240 mg/kg body weight for 28 days. The observed parameters were Leydig cell count and seminiferous tubule diameter. One-way ANOVA analysis showed that Gotu Kola extract significantly increased Leydig cell numbers and seminiferous tubule diameter in all treatment groups compared to the negative control group (p < 0.05). Post hoc analysis demonstrated significant differences in tubule diameter, with the highest improvement observed at the 240 mg/kg body weight dose. These findings indicate that Gotu Kola extract has potential protective effects against testicular damage caused by cigarette smoke exposure.